Adopting Smart Agriculture among organic farmers in Taiwan. Issue 2 (4th May 2021) - Takagi, Chifumi; Purnomo, Sutrisno Hadi; Kim, Man-Keun
ABSTRACT: Smart Agriculture is technology-driven agriculture. Taiwanese government has put tremendous efforts to spread this new technology. Many factors affect the rate of adoption of this technology. This paper aims to identify what factors are important using data from a survey of commercial organic farmers in Taiwan. Empirical results reveal that socio-demographic characteristics of farmers are not important for farmers' adoption decision. Perceived attributes of the new technology are the key factors; farmers more likely to adopt the new technology if it is compatible to their farm, easy to learn and use, and it is expected to increase yields and thus farm income. In addition, trial or test-run of the new technology is another key factor that increases adoption.